Effect of different pretreatment on the microbial diversity of fermented potato revealed by high-throughput sequencing. (30th August 2019) - Aregbe, Afusat Yinka; Mu, Taihua; Sun, Hongnan
Highlights: The dominant microorganisms are Nicotiana otophora, Weisella, and Saccharomyces . Steaming reduced undesirable microorganisms and promoted dominance of Weisella . Fermentation improved protein and dietary fiber contents in steamed and boiled samples. Steaming is recommendable for industrial processing of fermented potato. Abstract: To unravel prospective lactic acid bacteria (LAB) and yeasts with potential application in potato-based products, the microbial diversity of fermented potato was studied. High-throughput sequencing revealed that the 5 samples differ in microbial compositions resulting from nutrients modification by the pretreatment methods adopted. Weisella and Saccharomyces cerevisiae were found to be the dominant LAB and yeast in fermented potato respectively. The high abundance of Weisella (35.84%) and Gluconobacter (20.80%) in steamed fermented potato (SFP) resulted in lowering of pH (4.39 ± 0.09) and inhibition of undesirable bacteria and fungi. Fermentation increased protein and dietary fiber contents of boiled fermented potato (BFP) and SFP, with highest protein content (8.18 ± 0.22%) recorded in BFP. The dietary fiber contents of BFP and SFP are 9.68 ± 0.68% and 9.48 ± 0.37% respectively with no observable significant difference. This study provides information on microorganisms with potential benefits in quality enhancement of potato-based products.